Décentralisation, gouvernance forestière et démocratie au Sénégal : y a-t-il un avant et un après 1996 ? - Ahmadou Makhtar Kanté (VertigO)
In Sénégal, transfer of competencies from State to local governments through forest management decentralization has arrived in 1996. This study took the production of charcoal as observatory to understand to what point this new governance promotes (or not) the local democracy, in connection with the situation before 1996. It shows that in spite of legal power on any cut given to the rural councilors, representatives of the State through its territorial and forest administrations, and the private sector still largely influence decision makings on forest production without returning account to the local populations. This situation is contrary with the principle of free administration which implies that the local policy options must be the fact of the elected councils, in all the fields with transferred competences. It appeared too, that accountability occurs when the populations are able to charge given decisions to their representatives. In addition, the local elected council would function better with a greater clarification of the responsibilities for the executive and remainder of the others councilors, and more transparency in decision makings.